2012
DOI: 10.1111/j.1574-695x.2012.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-growing intestinal anaerobic bacteria

Abstract: Sessile growth of anaerobic bacteria from the human intestinal tract has been poorly investigated, so far. We recently reported data on the close association existing between biliary stent clogging and polymicrobial biofilm development in its lumen. By exploiting the explanted stents as a rich source of anaerobic bacterial strains belonging to the genera Bacteroides, Clostridium, Fusobacterium, Finegoldia, Prevotella, and Veillonella, the present study focused on their ability to adhere, to grow in sessile mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 29 publications
1
86
0
1
Order By: Relevance
“…and F. necrophorum were strong biofi lm producers, whereas C. bifermentans was a weak biofi lm producer. These isolates were subsequently examined in vitro, confi rming strong 48-h biofi lm production for B. fragilis , F. necrophorum , P. intermedia , and Veillonella spp., moderate for B. oralis and weak for P. distasonis (Donelli et al 2012 ). Also notable in this study was the moderate biofi lm production demonstrated by a strain of Clostridium diffi cile , and strong production by four additional species ( C. baratii , C. bifermentans , C. fallax , C. perfringens ) and F. magna .…”
Section: Biofi Lm Studies Of Anaerobic Organismsmentioning
confidence: 80%
“…and F. necrophorum were strong biofi lm producers, whereas C. bifermentans was a weak biofi lm producer. These isolates were subsequently examined in vitro, confi rming strong 48-h biofi lm production for B. fragilis , F. necrophorum , P. intermedia , and Veillonella spp., moderate for B. oralis and weak for P. distasonis (Donelli et al 2012 ). Also notable in this study was the moderate biofi lm production demonstrated by a strain of Clostridium diffi cile , and strong production by four additional species ( C. baratii , C. bifermentans , C. fallax , C. perfringens ) and F. magna .…”
Section: Biofi Lm Studies Of Anaerobic Organismsmentioning
confidence: 80%
“…While the precise spatial organization of gut microbes is currently unknown, the structure likely includes biofilm growth associated with host mucosa and epithelial tissue [57]. Indeed the literature provides substantial support for the hypothesis that some gut microbes organize into spatially structured multispecies biofilms [58,59]. We performed single species flux balance analysis and biofilm simulations to investigate the growth characteristic and byproduct secretion patterns of the three isolated species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the ability to form monoand duo-species biofilms for several gut bacteria such as Bacteroides oralis, various Clostridium species including C. difficile, Finegoldia magna and Fusobacterium necrophorum was shown in vitro. 52 C. difficile colonization of the gut and mechanisms involved in this process in vivo are poorly understood, but it is likely that formation of vancomycin (20 ÎŒg/mL), and C. difficile biofilm formation was induced when bacteria were exposed to sub-inhibitory and inhibitory concentrations of vancomycin (0.25 ÎŒg/mL and 0.5 ÎŒg/ mL, respectively). 19 Thus, in the case of C. difficile, biofilms may have multiple roles depending on the antibiotic concentrations in the environment.…”
Section: Difficile Biofilms: a Way Tomentioning
confidence: 99%